Bidens pilosa L. (Asteraceae): traditional use in a community of southern Brazil Bidens pilosa Linn (Asteraceae): uso tradicional em uma comunidade do Sul do Brasil - C.C. Borges; T. F. Matos; J. Moreira; A.E. Rossato; V. C. Zanette; P. A. Amaral (Universidade Estadual Paulista, 2013)
The correct use of plants for therapeutic purposes requires selection of those showing efficacy and safety based on the popular tradition and/or scientific validation. Bidens pilosa L. is a species that widely occurs in tropical regions and is known in Brazil as "picão-preto". Four agents from the Health Pastoral Service were identified in the region of Criciuma, Santa Catarina State, for their popular knowledge of Bidens pilosa. The study was conducted by means of interview which provided data concerning the knowledge of "picão preto", handling, used plant part, plant/solvent proportion, preparation methods, administration route/dosage, indication and restrictions. The pharmaceutical form, as well as the posology, was significantly variable. Analysis of the collected data showed anti-inflammatory action as the main therapeutic indication. O emprego correto de plantas para fins terapêuticos pela população requer o uso daquelas selecionadas por sua eficácia e segurança, com base na tradição popular e/ou cientificamente validadas como medicinais. Bidens pilosa L. é uma espécie que ocorre amplamente em regiões tropicais sendo conhecida no Brasil pelo nome popular "picão-preto". Quatro agentes da pastoral da Saúde foram identificadas na região de Criciúma/SC por possuírem maiores informações de cunho popular sobre Bidens pilosa. A pesquisa ocorreu por meio de entrevista, onde foram compiladas informações sobre o conhecimento do "picão-preto", manuseio, farmacógeno, proporção farmacógeno/ solvente, técnica de preparo, formas de uso/posologia, indicações e restrições de uso. A forma farmacêutica utilizada variou significativamente, assim como a posologia. A análise de informações coletadas mostra a ação antiinflamatória como principal indicação terapêutica.